Grape Seed Proanthocyanidin Alleviates Intestinal Inflammation Through Gut Microbiota-Bile Acid Crosstalk in Mice - Wu, Yi; Mo, Ruixia; Zhang, Mingrui; Zhou, Weiwei; Li, Defa (Frontiers in Nutrition, 2022)
Regulation of gut microbiota and modulation of bile acid (BA) composition are potential strategies for treatment of intestinal inflammation. This study aimed to investigate the effect of grape seed proanthocyanidin (GSP) on intestinal inflammation and to understand its mechanism. Antibiotics were applied to deplete gut microbiota to evaluate the contribution of gut microbiota to the effect of dietary GSP. Intestinal specific farnesoid X receptor (FXR) inhibitor was used to analyze the role of FXR signaling. In this study, GSP alleviated intestinal inﬂammation induced by LPS, and altered the gut microbiota accompanied by increased abundance of hydroxysteroid dehydrogenase producing microbes. GSP activated the intestinal FXR signaling pathway and increased gene expression of enzymes of the alternative BA synthetic pathway, which associated with elevated levels of chenodeoxycholic acid (CDCA) and lithocholic acid (LCA) in liver and feces. However, gut microbiota depletion by antibiotics removed those effects of GSP on mice injected with LPS. In addition, the protective effect of GSP on mice challenged with LPS was weakened by the inhibition of intestinal FXR signaling. Further, the mixture of CDCA and LCA mirrored the effects of GSP in mice injected with LPS, which might verify the efficiency of CDCA and LCA on intestinal inﬂammation. Taken together, our results indicated that GSP exerted an intestinal protection role in the inflammation induced by LPS, and these effects were mediated by regulating gut microbiota-bile acid crosstalk.